Collaborative Governance dalam Program Rehabilitasi Sosial Rumah Tidak Layak Huni di Kota Surabaya - Kristin, Citra; Wibawani, Sri (Universitas Muhammadiyah Mataram, 2023)
Abstract: The Social Rehabilitation Program for Uninhabitable Houses abbreviated as rutilahu is a program to improve the quality of housing through repairs as a whole and/or entirely with the principles of acceptability, transparency, accountability, integration, partnership, solidarity, benefits and participation. This study aims to describe in depth the process of collaborative governance in the Social Rehabilitation Program for Uninhabitable Houses in the City of Surabaya. This type of research uses descriptive qualitative techniques with the determining informants through purposive and snowball sampling techniques. Data collection techniques used were observations, interviews, and documentation. Data analysis techniques using